Updated guidelines on screening for gestational diabetes - Gupta Y; Kalra B; Baruah MP; Singla R; Kalra S (Dove Medical Press, 2015)
Yashdeep Gupta,1 Bharti Kalra,2 Manash P Baruah,3 Rajiv Singla,4 Sanjay Kalra2 1Department of Medicine, Government Medical College and Hospital, Chandigarh, India; 2Bharti Hospital, Karnal, Haryana, India; 3Excel Center, Guwahati, Assam, India; 4Saket City Hospital, New Delhi, India Abstract: Gestational diabetes mellitus (GDM) is associated with an increased risk of complications for both mother and baby during pregnancy as well as in the postpartum period. Screening and identifying these high-risk women is important to improve short- and long-term maternal and fetal outcomes. However, there is a lack of international uniformity in the approach to the screening and diagnosis of GDM. The main purpose of this review is to provide an update on screening for GDM and overt diabetes during pregnancy, and discuss the controversies in this field. We take on debatable issues such as adoption of the new International association of diabetes and pregnancy study groups criteria instead of the Carpenter and Coustan criteria, one-step versus two-step screening, universal screening versus high-risk screening before 24 weeks of gestation for overt diabetes, and, finally, the role of HbA1c as a screening test of GDM. This discussion is followed by a review of recommendations by professional bodies. Certain clinical situations, in which a pragmatic approach is needed, are highlighted to provide a comprehensive overview of the subject. Keywords: pregnancy, guidelines, IADPSG, GDM, Carpenter and Coustan criteria